2005
DOI: 10.1038/nature03357
|View full text |Cite
|
Sign up to set email alerts
|

The MET oncogene drives a genetic programme linking cancer to haemostasis

Abstract: The close relationship between activation of blood coagulation and cancer is an old enigma. In 1865, migrans trombophlebitis ('a condition of the blood that predisposes it to spontaneous coagulation') was described as a forewarning of occult malignancy (Trousseau's sign). This pioneering observation emphasized the existence of haemostasis disorders associated with cancer onset; this phenomenon has since been extensively reported in clinical and epidemiological studies, but has so far resisted a mechanistic exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
159
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 233 publications
(173 citation statements)
references
References 24 publications
7
159
0
3
Order By: Relevance
“…Finally, the positive effect of heparin treatment in Trousseau's syndrome patients may simply reflect the capacity of heparin to efficiently block P-and L-selectin mediated interactions. In the second model, targeting of activated human MET oncogene to the mouse liver resulted in slowly progressing hepatocarcinogenesis [6]. Prior to detection of dysplastic nodules all animals developed thrombohemorrhagic syndrome, similar to the symptoms observed in Trousseau's syndrome.…”
Section: Platelet Aggregation and Trousseau's Syndromementioning
confidence: 82%
See 2 more Smart Citations
“…Finally, the positive effect of heparin treatment in Trousseau's syndrome patients may simply reflect the capacity of heparin to efficiently block P-and L-selectin mediated interactions. In the second model, targeting of activated human MET oncogene to the mouse liver resulted in slowly progressing hepatocarcinogenesis [6]. Prior to detection of dysplastic nodules all animals developed thrombohemorrhagic syndrome, similar to the symptoms observed in Trousseau's syndrome.…”
Section: Platelet Aggregation and Trousseau's Syndromementioning
confidence: 82%
“…Since thrombosis occurs in the setting of occult carcinomas, it is reasonable to expect that a factor produced by tumor cells is being released into the bloodstream, which is responsible for thrombotic propensity [2]. There were two main studies investigating Trousseau's syndrome in animal models [6,68]. In the first model, purified carcinoma mucins, free of any TF, were shown to induce platelet-rich microthrombi formation in vivo [68].…”
Section: Platelet Aggregation and Trousseau's Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…MET activation indeed remodulates the integrin repertoire, disrupts intercellular junctions and induces transcription and activation of matrix metalloproteinases (reviewed by Trusolino and Comoglio, 2002). Furthermore, it has recently been shown that MET activation induces a cell-autonomous pro-coagulant activity that leads to pericellular fibrin deposition, thus creating a micro-environment that supports the growth of the tumor, favors the incoming of new vessels and is fertile for tumor cell expansion and survival (Boccaccio et al, 2005). Experimental evidence in animal models demonstrates that ectopic overexpression of MET renders cells tumorigenic and metastatic in nude mice (Rong et al, 1994), while MET or HGF transgenic expression results in development of spontaneous tumors and metastasis (Takayama et al, 1997;Wang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…50,51,[55][56][57][58] All these physiological and patho-physiological processes depend on uPA or plasmin activity and are governed by extensive cell-nonautonomous signaling. uPA is a secreted as well as cell surface-bound protease and PAI-1 is the major physiologic regulator of uPA activity; both modulate the extent and duration of extracellular matrix (ECM) remodeling.…”
Section: Pai-1 In Homeostasis and Diseasementioning
confidence: 99%